Pengukuran Kinerja Rumah Sakit Umum Daerah XYZ Dengan Menggunakan Metode Balanced Scorecard (Jasa Pelayanan Kesehatan Ibu dan Anak) - Setiawan, Hadi (Universitas Trunojoyo Madura, 2009)
Hospital offers health services for healing and rehabilitation, essential presence was felt by the community, hospitals., which provide health care for every patient, was often faced the same problems. The patient's dissatisfaction with the services provided by these hosp_ita(s was one of the problem. Regzonal General Hospital (Hospital) XYZ is a public hospital that moves local governments in the public health service in the region. Balanced Scorecard performance measurement system was used togive considerationfor the executive. Hospital performance based onfinancial persepectifweigths was 35%. The second persyective in performance measurement weight was 25%. Internal business process perspective of performances weight was 20%. The Final perspective on the Balanced Scorecard perf9rmance measurement in hospitals was learning and growth that has weight of20%. with performance indicators in this perspective was the number of physician speczalists and the number of employees trained for 0.40 or 40%